Does Uranus’ asymmetric magnetic field produce a relatively weak proton radiation belt? - Masters,A; Ioannou,C; Rayns,N (Geophysical Research Letters, 2022)
Since the Voyager 2 flyby in 1986 the radiation belts of Uranus have presented a problem for physicists. The observations indicate the electron radiation belt is far more intense than the proton radiation belt, and while the electron intensities are close to the upper theoretical limit, proton intensities are well below. Here we propose the relatively weak proton radiation belt could be due to Uranus' asymmetric magnetic field. We model test particle motion through the field to show that perturbations arising from asymmetry are greater the larger the particle gyroradius, predominantly affecting urn:x-wiley:00948276:media:grl65197:grl65197-math-0001100-keV protons. For these particles, more rapid changes in maximum distance from the planet during a bounce motion promote trajectory evolution into regions where they could be lost through impact with the rings, impact with the atmosphere, or to the distant magnetosphere and solar wind. We suggest this could explain a relatively weak proton radiation belt at Uranus.